Tissue-specific regulation of gene function: Presetting and erasure - Schwartz, Drew (1982)
Evidence is presented for presetting and erasure at the P locus of maize. The presence of an Mp transposable controlling element in the P(vv) allele affects the presetting and thus the regulation of gene function in different tissues.